Pengembalian Fungsi Baitul Mal Wa Tamwil melalui Strategi Penyelesaian Masalah Rentenir di Tasikmalaya - Nasrulloh, Agus Ahmad (UPT Publikasi Ilmiah UNISBA, 2020)
This study aims to find problems and solutions to restore the function of Baitul Mal Wa Tamwil through strategies to resolve moneylenders in Tasikmalaya. The method used is a qualitative-quantitative method with an analytic network process (ANP) approach. The results showed that the main problems that hampered the implementation of BMT functions caused by moneylenders in terms of educational problems were